2003
DOI: 10.1084/jem.20021745
|View full text |Cite
|
Sign up to set email alerts
|

An Early CD4+ T Cell–dependent Immunoglobulin A Response to Influenza Infection in the Absence of Key Cognate T–B Interactions

Abstract: Contact-mediated interactions between CD4+ T cells and B cells are considered crucial for T cell–dependent B cell responses. To investigate the ability of activated CD4+ T cells to drive in vivo B cell responses in the absence of key cognate T–B interactions, we constructed radiation bone marrow chimeras in which CD4+ T cells would be activated by wild-type (WT) dendritic cells, but would interact with B cells that lacked expression of either major histocompatibility complex class II (MHC II) or CD40. B cell r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
86
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 52 publications
15
86
0
Order By: Relevance
“…5C) indicating a trapping of B cells and ␥␦ T cells (but not ␣␤ T cells) in regional lymph nodes and thus the potential for local ␥␦ T cell-B cell interaction during early influenza virus infection. Although detailed information on ␥␦ T cell or NK T cell-mediated B cell help during influenza virus infection is lacking, the importance of noncognate help for the induction of early local virus-specific IgA responses to influenza virus infection in the MLN has been demonstrated (47). Moreover, the presence of neutralizing IgG Abs and B cell memory formation following infection of TCR ␣␤ gene-targeted mice with vesicular stomatitis virus was shown to dependent on ␥␦ T cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…5C) indicating a trapping of B cells and ␥␦ T cells (but not ␣␤ T cells) in regional lymph nodes and thus the potential for local ␥␦ T cell-B cell interaction during early influenza virus infection. Although detailed information on ␥␦ T cell or NK T cell-mediated B cell help during influenza virus infection is lacking, the importance of noncognate help for the induction of early local virus-specific IgA responses to influenza virus infection in the MLN has been demonstrated (47). Moreover, the presence of neutralizing IgG Abs and B cell memory formation following infection of TCR ␣␤ gene-targeted mice with vesicular stomatitis virus was shown to dependent on ␥␦ T cells (48).…”
Section: Discussionmentioning
confidence: 99%
“…In a primary influenza infection, virus-specific T-and B-cell responses are difficult to detect until 5 days after viral inoculation (39,46). Assuming that the contributions of the adaptive antibody and cellular responses of the immune system are negligible during this period, we used model 2 to fit the viral titer data during the first 5 days of infection.…”
Section: Resultsmentioning
confidence: 99%
“…Protective immunity against a primary infection with lethal type A influenza virus is to a large degree mediated by the humoral response, as shown by studies in which mice lacking B cells rapidly succumb to influenza infection despite the ability to mount a vigorous CD8 ϩ T cell response (1,2). Class switch recombination to Ab isotypes other than IgM is largely dependent upon T cell help, although Abs of the IgG isotypes are detectable at reduced titers in the absence of T-B interaction (3)(4)(5). Detailed analysis of the efficacy of Ab isotypes showed that IgG isotypes are primarily responsible for neutralizing influenza virus during primary and challenge infections (6,7), and earlier studies identified IgG2a as a key isotype for Ab-mediated effector functions in C57BL/6 mice (8 -10).…”
mentioning
confidence: 96%